Screening for primary angle closure in Mongolia: a randomised controlled trial to determine whether screening and prophylactic treatment will reduce the incidence of primary angle closure glaucoma in an east Asian population. Issue 3 (1st March 2003) - Nolan, W P; Baasanhu, J; Undraa, A; Uranchimeg, D; Ganzorig, S; Johnson, G J
Abstract : Aim: To describe the methods used and initial results of a prospective study designed to determine whether screening and prophylactic treatment will reduce the incidence of primary angle closure glaucoma (PACG) in Mongolia. Methods: A total of 4725 individuals aged 50 years and above were recruited to the study and randomised to intervention or control groups. All subjects had non-mydriatic optic disc examination. The intervention arm had measurement of anterior chamber depth (ACD) by A-scan ultrasound and intraocular pressure (IOP) with Tonopen. Gonioscopy was performed on test positive cases (ACD <2.53 mm or IOP ≥24 mm Hg either eye). Those with occludable angles were offered laser iridotomy. Primary outcome will be incidence of PACG at 5 year follow up. Results: Glaucoma was diagnosed in 128 (2.7%) subjects. Of the remaining 4597, 2293 were randomised to intervention. Intervention as allocated was received by 2280 (99.4%) individuals. 160 (23.4%) of 685 test positive cases had occludable angles, of which 156 were treated with iridotomy. Conclusions: This trial is a further step in determining whether screening and prophylactic treatment for primary angle closure in east Asian populations will reduce the incidence of glaucoma.